2009
DOI: 10.1007/s00270-009-9528-4
|View full text |Cite
|
Sign up to set email alerts
|

Clear Depiction of Inflammatory Abdominal Aortic Aneurysm with Diffusion-Weighted Magnetic Resonance Imaging

Abstract: We report the case of an inflammatory abdominal aortic aneurysm incidentally detected clearly with diffusion-weighted magnetic resonance imaging (DW-MRI) during the examination of a patient with myelofibrosis with myeloid metaplasia that later converted to acute myeloid leukemia. DW-MRI revealed a hyperintense halo surrounding the abdominal aorta with aneurysmatic dilatation, establishing the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…DWI sequences are increasingly used for the evaluation of other extracranial diseases and can be added to abdominal MRI protocols without relevant prolongation of the examination time (10)(11)(12)(13)(14). In the retroperitoneum DWI allowed the clear delineation of an inflammatory abdominal aortic aneurysm (19). Nakayama et al (20) found significantly different ADC values between malignant and benign retroperitoneal le-sions with lower values for lymphoma and carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…DWI sequences are increasingly used for the evaluation of other extracranial diseases and can be added to abdominal MRI protocols without relevant prolongation of the examination time (10)(11)(12)(13)(14). In the retroperitoneum DWI allowed the clear delineation of an inflammatory abdominal aortic aneurysm (19). Nakayama et al (20) found significantly different ADC values between malignant and benign retroperitoneal le-sions with lower values for lymphoma and carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Contrast-enhanced sequences allow the depiction of the perfused lumen (Fig 11) or a covered rupture by demonstrating contrast agent extravasation in the area of the aneurysmal sac (46). In an initial case report, investigators have suggested that diffusion-weighted imaging sequences allow differentiation of the cause of the aneurysm (47).…”
Section: Symptomatic Abdominal Aortic Aneurysmmentioning
confidence: 99%
“…69 MR imaging also may show diffusion restriction within the inflamed retroperitoneum, but this finding is nonspecific and should be correlated with ancillary imaging findings and followed closely to exclude an underlying malignancy. 70 Posterior aortic wall involvement, a lobular mass, and anterior displacement of the aorta from the adjacent vertebrae are features that suggest a retroperitoneal mass rather than an inflammatory aneurysm. 14,71 In addition, PET-CT may show increased FDG uptake within the wall of an inflammatory AAA.…”
Section: Inflammatory Aneurysmmentioning
confidence: 99%